2015
DOI: 10.1017/s0007114515004894
|View full text |Cite
|
Sign up to set email alerts
|

Responses in whole-body amino acid kinetics to an acute, sub-clinical endotoxin challenge in lambs

Abstract: Some effects of parasitism, endotoxaemia or sepsis can be mitigated by provision of extra protein. Supplemented protein may encompass a metabolic requirement for specific amino acids (AA). The current study investigates a method to identify and quantify the amounts of AA required during inflammation induced by an endotoxin challenge. One of each pair of six twin sheep was infused in the jugular vein for 20 h with either saline (control) or lipopolysaccharide (LPS, 2 ng/kg body weight per min) from Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Hoskin et al (2016) eloquently described that individual AA concentrations in the plasma pool are reflective of multiple factors that alter inflow (intestinal absorption, endogenous protein catabolism, de novo synthesis of nonessential AA) and outflow (extraction for protein synthesis, oxidation of AA), and that simple changes in plasma concentrations of an AA may not necessarily indicate a metabolic need specific for that AA. The metabolic demand of a different AA could cause an AA imbalance, thereby altering the plasma concentration of a specific AA indirectly (Hoskin et al, 2016). Nevertheless, the following are possible metabolic mechanisms that could explain some of the observed effects of LPS infusion on specific plasma AA concentrations in this study.…”
Section: Endotoxin Challengementioning
confidence: 82%
See 2 more Smart Citations
“…Hoskin et al (2016) eloquently described that individual AA concentrations in the plasma pool are reflective of multiple factors that alter inflow (intestinal absorption, endogenous protein catabolism, de novo synthesis of nonessential AA) and outflow (extraction for protein synthesis, oxidation of AA), and that simple changes in plasma concentrations of an AA may not necessarily indicate a metabolic need specific for that AA. The metabolic demand of a different AA could cause an AA imbalance, thereby altering the plasma concentration of a specific AA indirectly (Hoskin et al, 2016). Nevertheless, the following are possible metabolic mechanisms that could explain some of the observed effects of LPS infusion on specific plasma AA concentrations in this study.…”
Section: Endotoxin Challengementioning
confidence: 82%
“…Decreases in plasma Trp concentrations may also be reflective of an increase in the catabolism of Trp via the kynurenine pathway during inflammation (Le Floc'h and Seve, 2007;Hoskin et al, 2016), and decreases in plasma Thr concentrations could be in response to the inflammatory demand for increased synthesis of mucosal proteins in addition to acutephase proteins (Faure et al, 2006(Faure et al, , 2007. However, Hoskin et al (2016) also observed increased hepatic serine-threonine dehydratase activity in LPSchallenged lambs, which could be indicative of increased Thr catabolism. A decrease in plasma Tyr concentrations of steers in response to LPS infusion could also be related to the use of this AA as the immediate precursor for the synthesis of dopamine and the catecholamine hormones (epinephrine and norepinephrine), which increase in response to LPS in cattle (Li et al, 2007;Burdick et al, 2011).…”
Section: Endotoxin Challengementioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, it is plausible that the metabolic demand for AA to support various stress response-related functions, including haptoglobin synthesis, was not sufficiently higher in CON than in MEL calves to result in differences in the rate of skeletal muscle protein breakdown in our study. In addition to dietary supply, systemic AA concentration is determined by the processes of protein synthesis and breakdown, and de novo AA synthesis and oxidation (Waggoner et al, 2009;Hoskin et al, 2016). Plasma concentrations of Asn, Asp, Cit, Glu, Lys, Met, Ser, and Trp were greater (P ≤ 0.04), and those of Arg, Gly, Pro, and Thr tended to be greater (0.07 ≤ P ≤ 0.09) in MEL than in CON calves at 96 h after transport (Table 2).…”
Section: Short Communication: Effects Of Meloxicam Administration On mentioning
confidence: 99%
“…The higher MR intake for MEL compared with CON calves could account for the greater plasma AA concentrations in our study. Although information for transported calves is still lacking, pro-inflammatory and APP reactions induced in cattle and sheep using an endotoxin challenge resulted in a decrease in the plasma concentration of several AA, including Asn, Glu, Lys, and Phe (Waggoner et al, 2009;Hoskin et al, 2016). This is attributed to increased use of systemic AA to support various stress response-related functions, including hepatic APP synthesis and gluconeogenesis.…”
Section: Short Communication: Effects Of Meloxicam Administration On mentioning
confidence: 99%